Human Norovirus Molecular Analysis and Development of Norovirus Vaccine - Adinda Juwita Syakila Elizafanti; Maria Inge Lusida; Muhammad Miftahussurur; Alpha Fardah Athiyyah (Institute of Topical Disease Universitas Airlangga, 2022)
The most common organism of acute viral gastroenteritis is norovirus, which accounts for roughly 20% of all occurrences of acute gastroenteritis globally. The virus kills over 200,000 children each year and is the leading cause of childhood diarrhea in the rotavirus-vaccinated population. This study aims to review available studies regarding the information on the genogroup norovirus in humans, development of norovirus vaccines, and eï¬€ectiveness of norovirus vaccines. A systematic review using Science Direct, PubMed, and Scopus databases to identify eligible case studies. The search was conducted in September-October 2021. The quality of the included literature used checklists from the Critical Appraisal Skills Program (CASP). All of the six selected studies with populations given RT-PCR intervention showed positive for norovirus infection. The most predominant genogroups in humans are GI and GII. As for the research results of the two selected studies on norovirus vaccine, namely the human phase 2 trial containing two Virus-Like Particles (VLP) genotypes, one study showed eï¬ƒcacy at 18-49 one study at â‰¥ 60 years of age. This study analysis uses Takeda bivalent vaccine. The vaccine includes norovirus antigens of the GI and GII genogroups, intending to expand its protective immune potential. GI, GII, and GIV genogroups are prevalent in humans. VLP that contains GI.I and consensus GII.4c have been created as the NoV vaccine, providing signiï¬ cant eï¬ƒcacy. Very likely because they contain GI dan GII antigens, which are the genogroups that infect humans the most. Patients given a placebo developed acute gastroenteritis due to norovirus GII.2, indicating a genotype cross-reactivity.